Pengaruh Penerbitan Obligasi Syariah Terhadap Return Saham (Studi Kasus Pada Perusahaan Yang Menerbitkan Obligasi Syariah dan Terdaftar Pada Bursa Efek Indonesia (BEI) - Mutia Dwiana (Jurnal Bisnis, Manajemen, dan Ekonomi, 2020)
This type of research is quantitative, this research is conducted on companies that issue Islamic bonds and are listed at the Bursa Efek Indonesia (BEI). The method used is the event study method to show whether there is an effect of the issuance of Islamic bonds on stock returns in the event period of the issuance of Islamic bonds (sukuk), with a length of observation time of 15 days before and 15 days after the issuance event. The population used is companies that issue Islamic bonds that are still circulating as of February 2020. The sample was determined by purposive sampling technique and a sample of 15 incidents of Islamic bond issuance was obtained from 8 companies. Then the data is processed using t-test and paried sample t-test. The results showed that there was a significant Average Abnormal Return around the Islamic bond issuance period, which means that the issuance of Islamic bonds (sukuk) had an effect on stock returns. And there is also a significant difference in stock returns between before and after the issuance of Islamic bonds.